Praktik Ibadah sebagai Strategi Menanggulangi Sick Soul dalam Perspektif Agama - Astaniah Astaniah; Zaidan Naufal Raseuki; Mario Pindarto; Gita Septia Ningrum; Surawan Surawan (Nathiqiyyah, 2026)
The development of modern life, characterized by academic demands, social pressures, and rapid technological change, can impact the psychological well-being of individuals, particularly students. This condition can give rise to inner anxiety, known in the study of religious psychology as the concept of sick soul, a state of mind characterized by restlessness, loss of meaning in life, and emotional instability. In a spiritual context, religious practices are seen as one way to help individuals achieve inner peace and strengthen psychological balance. This study aims to analyze the relationship between religious practices and sick soul in college students. This study used a quantitative approach with a correlational survey design. The study subjects were 50 students from the State Islamic University of Palangka Raya, selected using a saturated sampling technique. Data were collected using a Likert-scale questionnaire measuring religious practices and sick soul. Data were analyzed using descriptive statistics, the Pearson Product Moment correlation test, and simple linear regression. The results showed a significant negative relationship between religious practices and sick soul, with a correlation coefficient of -0.383 and a significance level of 0.006. The regression analysis indicated that religious practices contributed 14.7% to the variation in sick soul. These findings indicate that the more religious practices students engage in, the lower their likelihood of experiencing mental illness. Therefore, religious practices can be understood as a spiritual strategy that plays a role in helping students maintain psychological balance and cope more adaptively with life's pressures.